Determinants of Poverty in Central Sulawesi 2020-2024 - Musakki, Reza Ahmad; Ichwan, Mohamad; Syamsuddin, H.; Parinding, Kalvin Albert; Cicilia, Vera Sri Endah (Transpublika Publisher, 2025)
This study aims to analyze the determinant factors of poverty in Central Sulawesi Province for the period 2020-2024, focusing on open unemployment, education, and per capita income. The research method uses quantitative panel data analysis with secondary data from the Central Statistics Agency (BPS) of Central Sulawesi, covering 13 regencies/cities. The selection of regression models was conducted through Chow and Hausman tests, which indicated the fixed effect model as the most appropriate model. The analysis results show that open unemployment and education have a positive but not statistically significant effect on poverty. Meanwhile, per capita expenditure has a negative and significant effect on poverty, with a coefficient of determination (Adj. R²) of 99.68%, indicating that the three variables can explain most of the variation in poverty. These findings confirm that increasing people's purchasing power through economic policies that promote per capita expenditure is a crucial step in reducing poverty. On the other hand, education and unemployment management require deeper intervention, such as improving education quality and creating employment opportunities, to strengthen the effectiveness of poverty alleviation programs. This study recommends that local governments prioritize policies focused on increasing community income and equalizing access to education and employment opportunities.